Stochastic characterization of a class of 2-state system availability processes - Chávez Fuentes, Jorge Richard (Pro Mathematica, 2010)
The system availability process indicates whether or not the interconnection of components is operating as intended at each time instant. It is shown that a 2-states system availability process that results from a transformation of a Markov chain is not a Markov chain. The probabilistic characterization of the system availability process is given.